Parametric study of geometrical effects on the degree of bending (DoB) in offshore tubular K-joints under out-of-plane bending loads. (June 2016) - Ahmadi, Hamid; Asoodeh, Shadi
Highlights: Geometrical effects on the DoB values in OPB-loaded tubular K-joints were studied. 162 FE analyzes were carried out for the parametric investigation of the DoB at the saddle position. A set of fatigue design equations was developed for the calculation of the DoB in OPB-loaded K-joints. Abstract: In this paper, results of comprehensive finite element (FE) analyses carried out on 81 generated models of tubular K-joints are presented. Results of FE models were verified against experimental data and parametric equations. The fatigue life of a tubular joint, which is commonly found in offshore industry, is not only dependent on the value of hot-spot stress (HSS), but is also significantly influenced by the through-the-thickness stress distribution characterized by the degree of bending (DoB). Data extracted from FE analyses was used to study the effects of geometrical parameters on the DoB values in tubular K-joints subjected to two types of out-of-plane bending (OPB) moment loads. The determination of DoB values in a tubular joint is essential for improving the accuracy of fatigue life estimation using the stress-life (S–N) method and particularly for predicting the fatigue crack growth based on the fracture mechanics (FM) approach. Geometrically parametric investigation was followed by a set of nonlinear regression analyses to develop DoB parametric formulas for the fatigue analysis of K-joints under OPB loadings.